Empowering Pre-service Biology Teachers through Sustainability Action: An Ethnobotanical Inventory Project in Cirebon - Bambang Ekanara; Riandi Riandi; Taufik Rahman; Rini Solihat; Lilit Rusyati (Universitas Sultan Ageng Tirtayasa, 2026)
Integrating Education for Sustainable Development (ESD) into teacher education requires shifting from theoretical knowledge to practical action competence. This study aims to describe how an Ethnobotanical Inventory Project empowers pre-service biology teachers to navigate the complexities of community-based conservation. Employing a qualitative case study design, the research focuses on three student working groups at UIN Siber Syekh Nurjati Cirebon who investigated distinct cultural sites: the Mundu coastal area, the Buyut Trusmi sacred site, and the Singkup agrarian village. Data were collected through field observations, semi-structured interviews, and analysis of student artifacts. The results demonstrate that the project successfully cultivated sustainability agency. Students developed interpersonal competence by negotiating access with traditional custodians (Paraji and Kuncen) and demonstrated scientific literacy by validating local knowledge with botanical taxonomy in their dissemination products (Pocket Books). Furthermore, the inventory highlighted a dichotomy in plant conservation: